The Effect of Utilizing Coastal Natural Materials as Learning Media on Early Childhood Cognitive Abilities - Nurlian; Teguh Yuliandri Putra; Syamsulrizal; Alman; Mursalim (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2026)
Early childhood education at TK Negeri 2 Yefman remains predominantly characterized by the use of synthetic, factory-manufactured teaching aids, despite the availability of coastal natural materials in the surrounding environment. This study aims to analyze the effect of utilizing coastal natural materials as learning media on children’s cognitive abilities. A quantitative approach with a one-group pretest-posttest design was employed, involving 13 children from Group B selected through purposive sampling. Data were collected using performance-based assessment instruments and analyzed using descriptive statistics, the Shapiro-Wilk normality test, paired-samples t-test, and N-Gain analysis. The results showed an increase in mean scores on cognitive abilities from 32.69 (pre-test) to 46.00 (post-test). The paired-samples t-test indicated a significant improvement after the intervention (p < 0.001), with an N-Gain score of 87.52%, indicating a high level of effectiveness. These findings suggest that coastal natural materials can be used as contextual learning media to support children’s cognitive development.